(3GdWahdI GdeHcQI aj GdHdOGf GdYQHjI (B: (3GdhGbY hGdJMOjGJs - (3GdUhjZ, SgGe YHO GdQMefs ((3HjQhJs (3GdjhfSchs, 2010)
(3jgOa GdJbQjQ Gdi OQGSI ChVGY GdWahdI GdeHcQI aj GdHdOGf GdYQHjI(B. (3hjJfGhd HGdJMdjd GdfhYj hGdcej GdhVY GdQGgf ddSjGSGJ hGdHQGeL hGdNOeGJ GdebOeI ddCWaGd aj eQMdI GdWahdI GdeHcQI aj GdHdOGf GdYQHjI(B. (3hjMGhd GdJbQjQ HfGA eYdheGJ Je JLejYgG ef NeSI YTQ HdOG YQHjG HgOa GdJYQa Gdi hGbY GdNOeGJ GdeJhaQI hJMdjd GdYhGFb hGdJMOjGJ hJMOjO GdChdhjGJ haQU GdJMSjf dJWhjQ GdHQGeL GdehLgI dNOeI GdCWaGd GdUZGQ aj Ohd GdefWbI GdYQHjI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Arab Countries; Early Childhood; La petite enfance; Les pays Arabes; (3GdOhd GdYQHjIs; (3GdWahdI GdeHcQIs